Ownership strategy of Japanese firms: transactional, institutional, and experience influences - Delios, Andrew; Beamish, Paul W. (Strategic Management Journal, 1999)
We compare the effects of transactional, institutional, and experience influences on the ownership strategies of Japanese investors. Our theoretical development suggests that the equity position of a foreign investor should increase as the specificity of the assets transferred to the foreign affiliate increases, but a lower equity position should be assumed when the foreign investor requires complementary assets to establish a foreign entry. International experience and a strong institutional environment also should lead to increases in the equity position of the foreign investor. These relationships were tested with data on more than 1000 Japanese investments in nine countries of East and South-East Asia. The results demonstrate that experience and institutional factors were the most important influences on the ownership position taken in the foreign investment, while transactional factors had a much less important and a more ambiguous role. Copyright © 1999 John Wiley & Sons, Ltd.